Representation of Parental Communication in Nanti Kita Cerita Tentang Hari ini (2020) - Leviana Susanto; Tangguh Okta Wibowo (PT FORMOSA CENDEKIA GLOBAL, 2023)
Family is the primary socialization agent, parents as important figures have the responsibility to educate and raise their children, one of which is through communication. But, in this day, there is still a lot of disharmonies in the family caused by several factors such as the lack of parental communication education from parents to children. On the other hand, a harmonious atmosphere can be built if there is an attitude of openness and good communication within the family, both verbally and non-verbally. Departing from this matter, the researcher further discussed the topic of family communication through the film, Nanti Kita Cerita Tentang Hari Ini as a reflection of similar cases in real life. This research uses Charles Sanders Pierce's semiotic method through signs, objects, and meanings. The results show that the father character has a dominant role with harsh communication that has a negative impact on the child, while the mother applies responsive communication that helps the growth of a positive personality in the child. Although the mother's role is not dominant, her parental communication serves as a balance to the father's communication in the family